2017
DOI: 10.1002/brb3.791
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E epsilon 4 (APOEε4) genotype is associated with decreased 6‐month verbal memory performance after mild traumatic brain injury

Abstract: IntroductionThe apolipoprotein E (APOE) ε4 allele associates with memory impairment in neurodegenerative diseases. Its association with memory after mild traumatic brain injury (mTBI) is unclear.Methods mTBI patients (Glasgow Coma Scale score 13–15, no neurosurgical intervention, extracranial Abbreviated Injury Scale score ≤1) aged ≥18 years with APOE genotyping results were extracted from the Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK‐TBI Pilot) study. Cohorts determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 91 publications
(127 reference statements)
5
28
0
Order By: Relevance
“…There are multiple isotypes of ApoE (ε2, ε3, ε4) with different functional properties. Individuals with at least 1 copy of the ε4 allele are at higher risk of Alzheimer disease and worse outcomes after traumatic brain injury . In patients with CHD, the ApoE ε2 allele is associated with worse early ND performance in patients with CHD, a deficit that persists as patients age and that has been replicated in a similar but distinct patient cohort .…”
Section: Genetic Modifiers Of Clinical Outcomesmentioning
confidence: 94%
“…There are multiple isotypes of ApoE (ε2, ε3, ε4) with different functional properties. Individuals with at least 1 copy of the ε4 allele are at higher risk of Alzheimer disease and worse outcomes after traumatic brain injury . In patients with CHD, the ApoE ε2 allele is associated with worse early ND performance in patients with CHD, a deficit that persists as patients age and that has been replicated in a similar but distinct patient cohort .…”
Section: Genetic Modifiers Of Clinical Outcomesmentioning
confidence: 94%
“…It follows that the host-response is a key factor in regulating secondary injury processes such as cerebral edema and contusion expansion that significantly influence outcome after TBI. Genetic variation is increasingly recognized as an important contributor to variability in post-traumatic host response [28,[115][116][117][118][119][120][121][122][123][124]. adjacent gene KCNJ11 (encoding KIR6.2).…”
Section: Impact Of Genetic Variation In Abcc8 (Encoding Sur1) and Trpmentioning
confidence: 99%
“…APOE genotype was not found to be a predictor of impairment at either time point; however ε4-positive patients, as with positive computed tomography (CT) findings, associated with reduced improvement in performance at 6 months [ 54 ]. In Yue et al, 2017, a prospective cohort of 114 MTBI patients (mean age 43 years, 28% with ε4 allele), verbal memory evaluation using the CVLT-II at 6 months post-injury revealed impaired long-delay free and cued recall for ε4 carriers, along with marginally decreased short-delay cued recall [ 55 ]. Yang et al, 2015, a retrospective cohort of 27 individuals with MTBI (mean age 54 years for those without dementia, 60 years with dementia, MTBI history 6 years ago, 30% with ε4 allele) and 10 age-matched controls, found the highest APOE-ε4 frequency in subjects with MTBI history plus development of dementia (0.250 vs. 0.143 for MTBI without dementia vs. 0.050 for controls) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, up to 30% of MTBI patients who are CT-negative can be MRI-positive for intracranial injury, specifically axonal shear and gliding contusions [ 77 ]. Yue et al, 2017 found that 25% of MTBI patients had intracranial pathology on initial head CT scan within 24 h of injury, and APOE-ε4 did not accurately predict the presence of acute CT-positive lesions [ 55 ]. Casson et al, 2014 conducted extensive MRI studies with susceptibility weighted imaging (SWI) and diffusion tensor imaging (DTI) in a cohort of retired professional football players experiencing a mean total of nineconcussions over their lifespan, 38% of whom were ε4 carriers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation